POKOK-POKOK PIKIRAN PENDIDIKAN PERTANIAN DI ERA TEKNOLOGI INFORMASI - Yoyon Haryanto; Zahron Helmi (Jurnal Kommunity Online, 2020)
AbstractAgriculture which is a potential sector needs to be developed and supported by adequate human resources. One of them is through the role of education so that the human resources produced by formal education are able to become business actors in the agricultural sector (off farm) and be able to become main actors / farmers (on farm). Seeing this, there is a huge opportunity for the Ministry of Agriculture through The Agricultural Human Resource Extension and Development Agency (BPPSDMP) encourages educational institutions that are owned with a vocational education pattern that further emphasizes their abilities and skills because almost 70% of the education base is practice and 30% is theory, to contribute to alumni taking part further in the broader field of agriculture in Indonesia. Especially one of them is to be an alternative to motivate the interest of the younger generation in the business sector in the agricultural sector. However, the presence of the era of information technology is a challenge in itself to combine agriculture, educational expectations and information technology itself. The era of Information Technology must be used as a means to maintain and improve the quality and quantity of agricultural human resources. Information technology must be adapted and utilized more optimally. These studies and thoughts are an alternative in welcoming the regeneration of agriculture that is more competitive, professional and has a strong agricultural character.Keywords: agriculture; education; information TechnologyAbstrakPertanian yang merupakan sektor potensial perlu dikembangkan dan didukung oleh sumber daya manusia yang memadai. Salah satunya melalui peran pendidikan agar sumber daya manusia yang dihasilkan oleh pendidikan formal tersebut mampu menjadi pelaku usaha di bidang pertanian (off farm) dan mampu menjadi pelaku utama/petani (on farm).Melihat hal tersebut terbuka peluang yang sangat besar untuk Kementerian Pertanian melalui Badan Penyuluhan dan Pengembangan Sumber Daya Manusia Pertanian (BPPSDMP) mendorong lembaga pendidikan yang dimiliki dengan pola pendidikan vokasi yang lebih menonjolkan kemampuan dan keterampilan karena basis pendidikan yang hampir 70% adalah praktik dan 30%nya lagi adalah teori, untuk memberikan sumbangan alumni-alumninya berkiprah lebih jauh dalam bidang pertanian secara luas di Indonesia. Terutama salah satunya adalah menjadi alternatif penggerak minat generasi muda pada bidang usaha di sektor pertanian. Namun, hadirnya era teknologi informasi menjadi tantangan tersendiri untuk memadukan antara pertanian, harapan pendidikan dan teknologi informasi itu sendiri.Era Teknologi Informasi harus dijadikan sarana untuk menjaga dan meningkatkan kualitas dan kuantitas SDM Pertanian. Teknologi Informasi harus diadaptasi, dimanfaatkan lebih optimal. Telaahan dan pemikiran ini menjadi salah satu alternatif dalam menyongsong regenerasi pertanian lebih berdaya saing, profesional dan memiliki karakter pertanian yang kuat.Kata kunci: pertanian; pendidikan; teknologi informasi